'Degenerate Dance': The Case of Mary Wigman. (November 2017) - Kew, Carole
Abstract : Mary Wigman (1886–1973) remained in Germany during the period of the Third Reich. Based on an article published in 1940 entitled Entarteter Tanz ( Degenerate Dance ), this essay discusses why the dance of Mary Wigman and, more broadly, why Weimar dance was labelled 'degenerate' by the National Socialist regime. The argument is framed with reference to an article written by Mary Wigman about her school which was published a few months later in the same prominent dance journal, Der Tanz .